Airline joint ventures in emerging markets: The case of Saudia under vision 2030 - Bora, Ayse; Tatoglu, Ekrem; Keskin, Halit; Esen, Emel (ELSEVIER, 2026)
The liberalization of global air transport has encouraged airlines to adopt joint ventures (JVs) as a means of expanding networks, reducing risk, and strengthening competitiveness. While literature provides rich insights into JVs in mature markets, their feasibility in emerging markets remains underexplored. This study addresses this gap by examining the prospects for Saudia, the national carrier of Saudi Arabia, to pursue JVs in support of the country's Vision 2030 strategy. Drawing on transaction cost economics, the resource-based view, and network theory, the study employs a qualitative case design based on elite interviews with senior industry executives, policy advisors, and academic experts. The findings identify both opportunities and constraints, highlighting issues of strategic fit, regulatory reform, operational capacity, partnership design, cultural alignment, risk management, and market readiness. The analysis shows that while JVs could provide Saudia with a viable pathway to accelerate international integration and enhance competitiveness, success will depend on regulatory clarity, organizational modernization, and credibility with global partners. The study advances research on airline alliances in emerging markets and offers practical guidance for managers and policymakers engaged in shaping the future of aviation in Saudi Arabia.
Keywords: Airline joint ventures; Strategic alliances; Saudia; Vision 2030; Emerging markets; Saudi Arabia; TRANSACTION COSTS; ALLIANCES; LIBERALIZATION; COMPETITION; Business & Economics; Transportation